What Role Does Service-Learning Play in Enhancing Vineyard Agro-Tourism in Duyu Village? - Azim; Meylisa Aulia Zalianti; Sukmawati; Dewi Salmita; Fatma (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Datokarama Palu, 2024)
This article presents a Community Service Program implemented in Duyu Village aimed at promoting the development of vineyard-based agro-tourism through the Service-Learning approach. The initiative responds to critical challenges faced by local farmer groups, particularly deficiencies in digital marketing and tourism management, which constrain their economic potential and sectoral growth. Employing a mixed-methods framework, the program engaged local farmers in a participatory needs assessment to identify existing gaps and co-develop targeted interventions. A series of workshops were conducted to build capacity in sustainable agricultural practices and digital marketing strategies, equipping farmers with the tools to effectively promote their vineyards as tourism destinations. Results demonstrate notable improvements in participants’ knowledge and skills, accompanied by increased income generated from agro-tourism activities. Nonetheless, constraints such as limited training duration and variable participant engagement were observed. Recommendations for future implementation include extending the duration of capacity-building sessions and establishing strategic partnerships with local stakeholders. Overall, this program underscores the effectiveness of integrating academic learning with community engagement in fostering sustainable rural tourism development.